Sustainable Finance – Divestment as a Tool to Reach the SDGs? - Mechthild Schrooten (Vierteljahrshefte zur Wirtschaftsforschung, 2021)
This paper synthesizes the literature on sustainable divestment. Nowadays, divestment seems to be a popular strategy to sanction harmful industries or socially not desired outcomes of economic activities. However, in practice for a long time many firms which were known for harmful technologies did not face divestment or a loss in value. Seminal theoretical work was done by Heinkel et al. (Heinkel, Kraus, & Zechner, 2001). Recent theoretical studies based on this approach show that divestment has huge limitations. Theory explains that "voice" (engagement in the company) is superior to "exit" (divestment). Nevertheless, the divestment movement and campaigns are of considerable social size. The effects of divestment on the financial market seems to be small in monetary terms. However, there are a lot of side effects, such increasing social awareness concerning the wasteful lifestyle. The divestment movement is gaining importance and actors. Therefore, the divestment movement is a supporting tool to reach SDGs. Not directly via the impact on the financial market, but by raising the social awareness. – – Dieses Papier bereitet die gängige Literatur zum Thema "Divestment" auf. Über eine lange Zeit konnten viele Firmen, die für den Einsatz umweltschädlicher Technologien bekannt waren, lange Zeit davon ausgehen, dass sie nicht über den Finanzmarkt sanktioniert werden. Heutzutage scheint Divestment eine verbreitete Strategie zu sein, um umweltschädliche Unternehmensaktivitäten zu sanktionieren. Grundlegende theoretische Arbeiten zum Thema Divestment wurden von Heinkel et al. (Heinkel, et al., 2001) veröffentlicht. Jüngste theoretische Studien, die auf diesem Ansatz basieren, zeigen, dass die Wirtksamkeit von Divestment begrenzt ist. Vielmehr scheint "Voice" (Engagement im Unternehmen) dem "Exit" (Divestment) überlegen zu sein. In der Praxis jedoch stoßen die Divestment-Kampagnen auf eine beachtliche gesellschaftliche Resonanz. Die Auswirkungen von Divestment auf den Finanzmarkt scheinen dagegen eher gering zu sein. Es gibt jedoch viele indirekte Effekte von Divestment, wie z. B. ein zunehmendes gesellschaftliches Bewusstsein für den umweltschädliche Unternehmenspolitik und Konsumgewohnheiten. Daher kann Divestment als indirektes wirkendes Instrument zur Erreichung der SDGs betrachtet werden. Divestment entwickelt demnach seine Strahlkraft nicht direkt über die Auswirkungen auf den Finanzmarkt, sondern durch die Sensibilisierung der Gesellschaft.
Keywords: G11; Q54; B59; 330; Investment Decisions; Divestment; Campaigns; CO2 reduction